2013
DOI: 10.1038/ijos.2013.10
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of epidermal growth factor receptor 4 in oral leukoplakia

Abstract: In the present study, we investigate the expression profile of the epidermal growth factor receptor family, which comprises EGFR/ErbB1, HER2/ErbB2, HER3/ErbB3 and HER4/ErbB4 in oral leukoplakia (LP). The expression of four epidermal growth factor receptor (EGFR) family genes and their ligands were measured in LP tissues from 14 patients and compared with levels in 10 patients with oral lichen planus (OLP) and normal oral mucosa (NOM) from 14 healthy donors by real-time polymerase chain reaction (PCR) and immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 20 publications
1
12
1
Order By: Relevance
“…41,42 Further, high mRNA and protein expression of EGFR family members have been reported in so-called oral leukoplakia, an analogous clinicopathologic condition to esophageal epidermoid metaplasia, but in the oral cavity. 43,44 However, activating mutations in EGFR and HRAS comprise a minority of esophageal epidermoid metaplasia cases and, to date, have not been reported in esophageal squamous cell carcinoma. It should be reiterated that aberrant receptor tyrosine kinase/mitogen-activated protein kinase signal transduction may occur through multiple genetic and epigenetic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 Further, high mRNA and protein expression of EGFR family members have been reported in so-called oral leukoplakia, an analogous clinicopathologic condition to esophageal epidermoid metaplasia, but in the oral cavity. 43,44 However, activating mutations in EGFR and HRAS comprise a minority of esophageal epidermoid metaplasia cases and, to date, have not been reported in esophageal squamous cell carcinoma. It should be reiterated that aberrant receptor tyrosine kinase/mitogen-activated protein kinase signal transduction may occur through multiple genetic and epigenetic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…While not looking at the PI3K pathway directly, Kobayashi et al compared the expression of EGFR‐like receptors and ligands in tissue samples between equal numbers of patients with lichen planus ( n = 10) and individuals without the disease. mRNA expression levels of EGFR mRNA were significantly higher among the OLP cohort.…”
Section: Could the Pi3k Pathway Play A Role In Facilitating Carcinogementioning
confidence: 99%
“…mRNA expression levels of EGFR mRNA were significantly higher among the OLP cohort. They suggested that the differential upregulation of both EGFR and its ligands might be sufficient to impact cell surface proto‐oncogenes and in that way provide a conduit of a path leading to OSCC .…”
Section: Could the Pi3k Pathway Play A Role In Facilitating Carcinogementioning
confidence: 99%
“…EGFR family members include c-erbB1 (Her1), c-erbB2 (Her2-neu), c-erbB3 (Her3), and c-erbB4 (Her4). These subclasses have been studied in OED 20,23. Several reports demonstrate that c-erbB-2 expression increased progressively from non-dysplasia to dysplasia and OSCC 2427.…”
Section: Introductionmentioning
confidence: 99%